Evaluation Of Vehicle Load Pattern Of Crossing Simanindo - Tigaras Traffic In North Sumatera Province - Surnata, Surnata; Priambudi, Miko; Purboyo, Purboyo; Agustini, Elfita (IWTJ : International Water Transport Journal, 2020)
Transportation is a physical activity of the movement of goods or passengers from one place to another which has a very important role in economic, social, cultural and political development. With the transportation of the distribution of these goods and the results of production can be done and reach all regions evenly which will ultimately increase Regional, National income and open isolated areas and increase income for the local area and the country in general. The increasing interaction of transportation between economic and social activities in an area causes the need for a transportation role that is useful to assist movement in the area. The economic and social development of an area is also strongly influenced by the transportation system which will ultimately increase the development of the region. The success of the development of an area is strongly influenced by the role of transportation as the lifeblood of life in an area both political, economic, social and cultural life as well as defense and security. To realize the mission championed by transportation, namely improving the quality of services and management of transportation services that are reliable, competitive and provide added value that is able to support the recovery of the national economy. Simanindo Port, located in Samosir Regency, North Sumatra Province, is a commercial port managed by the Department of Transportation that serves public services to carry out crossing activities that connect Simanindo Port in Samosir District with Tigaras Port within the Simalungun Regency. The existence of the Simanindo-Tigaras cross is very important because with the existence of the port, it can support economic development efforts and also as a vein of land transportation due to the interruption of Lake Toba. In the transportation system, security and safety are preferred as a form of good service delivery. Safety is demonstrated not only to service users and ship operators, but also to vehicles both at port and while sailing. As with the regulation and handling of vehicle loads on board, the better the arrangement and handling of vehicles on board the better the level of vehicle security and safety on the ship and vice versa the worse the arrangement and handling of vehicles on board the worse the level of vehicle security and safety on board.